Nomenclatural and taxonomic notes on Eugenia (Myrtaceae) from India - Singh, Rajeev Kumar (Phytotaxa, 2024)
The paper deals with the designation of lectotypes for eight names within the genus Eugenia and provides an explanation of the validity of the lectotypification for the name E. discifera. Additionally, it recognizes E. macrosepala as a distinct species by providing the morphological differences from E. roxburghii.